Parallelism in Nursery Rhymes - Hetty Catur Ellyawati (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2018)
Â Parallelism is a way to make your writing and speaking become more interesting and clear. Some of poetry writers and public speakers use this method to make their writings or speeches easy to remember. Another writing using parallelism is nursery rhymes. This research aims to find out the use of parallelism in nursery rhymes in ABCKidsinc. The method used to collect data is purposive random sampling, meanwhile in analysing data, I use descriptive method.Â  The result of this research is there is a use of parallelism in nursery rhyme in ABCKidsinc. It is not only in vocabulary and sound but also in grammar.Keywords: parallelism, nursery rhymes, vocabulary, sound, grammar